Pencarian Rute Jasa Pemesanan Penggilingan Padi Berbasis Android Dengan Menggunakan Google Maps - Moch Lutfi; Elmaida Khoirotuzzuhria (Faculty of Computer Science, University of Jember, 2023)
The location where the rice mill service is located is an important thing for most farmers to improve the quality of rice. Clear information about the rice mill is one of the determining factors in choosing a suitable rice mill. For farmers and people who do not know the surrounding area when they are going to do rice milling, it will be difficult to find the nearest rice mill location. There are several weaknesses when using a manual system, including the information obtained is not in accordance with the expected needs, and the distance traveled requires a relatively long time and relatively large cost. The research conducted by the author is to design an application for ordering rice milling services using the waterfall method and using google maps as a method of finding the closest route. The purpose of the study was to determine the application of google maps to the rice mill ordering application. From the results of system testing using blackbox testing, the results show that the application being tested can run and function as expected. While the results of testing the questionnaire by getting an index of 79.75%.